Direct metal laser sintering, using conformal cooling, for high volume production tooling - Van As, B.; Combrinck, J.; Booysen, G.J.; De Beer, D.J. (South African Journal of Industrial Engineering, 2017)
Existing techniques to manufacture conventional tool steel inserts for the plastic injection moulding process are expensive and time-consuming. Complex mould inserts, difficult to manufacture with conventional processes, can be produced using Direct Metal Laser Sintering (DMLS) with Maraging tool steel (MS1). MS1 is an additive manufacturing (AM) material made available by Electro Optical Systems (EOS) GmbH. Contrary to material removal processes, DMLS can produce MS1 tool steel inserts directly from Computer-Aided Design (CAD) files suitable for high volume plastic injection moulding. Through DMLS it is possible to create conformal cooling channels inside the MS1 inserts that have advantages in reducing heat rapidly and evenly. This can result in a reduction of cycle times, cost per product as well as improving part quality by eliminating defects such as warpage and heat sinks. This paper will present a comparison between Finite Element Analysis (FEA) simulations of the injection mould inserts with actual mould trails of AM and conventional manufactured inserts. It also includes the design and manufacturing of conventional and DMLS inserts and compares the manufacturing costs and lead times. Using FEA simulations, the design of conformal cooling channels is optimised by comparing the mould temperature of different cooling channel layouts. Bestaande vervaardigingstegniek van matryse vir die plastiek-inspuit giet tegniek is duur en tydrowend. Ingewikkelde matrysinsetsels, wat moeilik is om met konvensionele prosesse te vervaardig, kan met direkte lasermetaalsintering (DMLS) met Maraging-staal (MS1) vervaardig word. MS1 is ŉ toevoegings-vervaardiging materiaal wat deur Electro Optical Systems (EOS) GmbH verskaf word. In teenstelling met materiaal verwyderings-prosesse (masjinering), kan DMLS MS1 staal matryse of insetsels wat direk vanaf rekenaargesteunde ontwerpprosesse vervaardig word. Dit maak dit geskik vir hoë volume produksie. Deur DMLS kan daar ook vir vormgetroue verkoelings kanale in matryse voorsiening gemaak word, wat tot die vinnige en eweredige verspreiding van hitte lei. Dit behoort tot ’n aansienlike verlaging in produksie-siklustye en -koste te lei saam met ’n verbetering in die gehalte van die vervaardigde parte as gevolg van die voorkoming van defekte soos kromtrekking en hitte-putte. Hierdie artikel vergelyk ŉ eindige element analise van die insetsels wat met DMLS tegnieke en konvensionele tegnieke vervaardig is. Dit sluit ook die ontwerp en vervaardiging van konvensionele en DMLS insetsels in en vergelyk vervaardigingskostes en leitye. Die ontwerp van vormgetroue verkoelingskanale word deur middel van eindige element analise optimeer deur die gietvorm temperatuur met verskillende verkoelingskanaaluitlegte te vergelyk.